2009
DOI: 10.1258/td.2008.080077
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya in West Bengal, India

Abstract: Fever of unknown origin broke out in several districts of West Bengal, from August 2007 to December 2007. The cases were suffering from high fever, severe joint pain lasting for several weeks after clinical cure and appearance of skin rashes. Patients' sera were collected at least five days after fever and were analyzed to detect specific IgM antibodies. A total of 800 patients were investigated and 321 (40.13%) were found to be reactive for Chikungunya antibodies. Of the patients, 66% were male. Predominant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…A large number of respondents considered that Chikungunya to be contagious and More than half of the respondents knew Chikungunya infection is not transmitted from person to person. The clinical profile of the Chikungunya observed in this study, high fever, head ache, vomiting, joint pain and Body rash, body ache, 5.7% myalgia sign and symptom of CHKV [25]. Most of the respondents were aware about treatment of Chikungunya infection that only paracetamol is required for treatment of CHKV, antibiotic not required for treatment of Chikungunya because Chikungunya is a self-limiting disease with morbidity rate is high, so only paracetamol, plenty of rest is enough for management of Chikungunya infected patient [26].…”
Section: Discussionsupporting
confidence: 51%
“…A large number of respondents considered that Chikungunya to be contagious and More than half of the respondents knew Chikungunya infection is not transmitted from person to person. The clinical profile of the Chikungunya observed in this study, high fever, head ache, vomiting, joint pain and Body rash, body ache, 5.7% myalgia sign and symptom of CHKV [25]. Most of the respondents were aware about treatment of Chikungunya infection that only paracetamol is required for treatment of CHKV, antibiotic not required for treatment of Chikungunya because Chikungunya is a self-limiting disease with morbidity rate is high, so only paracetamol, plenty of rest is enough for management of Chikungunya infected patient [26].…”
Section: Discussionsupporting
confidence: 51%
“…It was also observed that 66% were male patients and most common symptoms among cases were sudden onset of fever, joint pain and skin rashes. [12] Vijaykumar K P et al in their study in Kerala too observed a similar clinical pattern with fever and joint pain seen in all the patients included in the study. Swelling of joints was seen in 69.9% of the patients, being closely followed by head ache (64.1%) and itching (50.3%).…”
Section: Discussionsupporting
confidence: 64%
“…Mathur et al 4 published a case report with a similar association of AGN with HAV infection in a seven-year-old boy who had mesangial proliferative glomerulonephritis, nephrotic syndrome and acute renal failure with HAV infection.…”
mentioning
confidence: 95%